Ekonomi Syariah : Bergerak Menuju Kapitalisme Religius ? - Prasetyo, Heri; Hermansyah, Hermansyah (Journal Competency of Business, 2021)
The economic system is a fundamental element that determines the economic performance of a country. Various forms of economic systems that have ever existed, including large economic systems such as capitalism, socialism adopted by various countries have become a guide and foundation for the country's economic policies. Then the emergence of a complementary thought discourse on an economic system based on religious values with theological arguments that Islam is a divine religion based on revelation (the Qur'an) functions to guide human life both socially, politically, and economically. the scarcity of literature that explains the values of philosophy, institutions, principles, norms, and values of Islamic economic law. The author uses a literature study method or literature study by examining the literacy of opinions, ideas from thinkers and experts on classical, contemporary, and sharia modern economic systems such as Adam Smith, Lester Thurow, Max Weber, Adi Warman Karim, Fazlurrahman, Umar Chapra, Syed Nawab Haider Naqvi, Ibn Khaldun, Ibn Taymiyah Mubyarto. Furthermore, notes on the normativism of the Islamic economic system are important because they are related to the desired religious capitalism. Then, some of the arguments for religious capitalism are presented by looking at philosophical factors, historical-aspirational factors, and also factors that can be called futuristic. In the philosophical study, the author concludes that Islamic economic religious capitalism is a form of the dialectical process of the earth system and the sky system. Harmonization of rationalism and spiritualism. The futuristic discussion shows that Islamic economic religious capitalism can be the end of history. But that does not necessarily stop the social challenges that arise. Capitalism itself is still undergoing changes, and shocks. The religious capitalism of Islamic economics is to see how Islamic economics will undergo a metamorphosis for the people of Indonesia, although there is no harm in advancing it as a futuristic study, as a future global economic system because it is claimed to carry universal values.